Relationship between Folate, B12 and Homocysteine levels and Obstetrical Outcomes in Preterm Premature Rupture of Membrane - S. Dawood, Aya; J. Mohammed, Ahmed (Journal of the Faculty of Medicine Baghdad, 2024)
Background: When the fetal membranes rupture before the completion of 37 weeks of gestation, it is known as Preterm Pre-labor Rupture of the Membranes (PPROM). This condition occurs in around 2% of all pregnancies. Predicting the occurrence of PPROM involves identifying associated risk factors and using specific biomarkers to prevent any adverse maternal or fetal outcomes. Objectives: To investigate the relationship between folate, B12, and homocysteine in PPROM and assess the maternal and neonatal outcomes of PPROM. Cases and Methods: A case-control study was conducted on 100 pregnant women at the Department of Obstetrics and Gynecology at Al-Khansaa Maternity Teaching Hospital. The study was conducted between 20th January and 1st July 2022. The participants were women with a single viable fetus and a gestational age 240/7 – 366/7 weeks. The study had two groups of Fifty pregnant each. The first group, known as the “case” group, consisted of pregnant women suffering from PPROM. The second group, known as the “control” group, consisted of pregnant women who were matched for gestational age, had intact membranes, were not in labor, and had no obstetrical complications. The study estimated both groups’ serum folate, B12, and homocysteine levels. Ethical approval was obtained prior to conducting the study. Results: No differences were found between the two groups regarding B12 and demographic data. However, the folate level was found to be lower in the cases than in the controls. On the other hand, the homocysteine level was significantly higher in the cases than in the controls. A homocysteine level of ≥ 28.85 nmol/ml was shown to be associated with a high sensitivity of 90%, specificity of 84%, and accuracy of 87%. Therefore, it could also be used as a reliable tool to predict PPROM. A folate level of ≤3.22 ng/ml, on the other hand, is associated with moderate sensitivity and low specificity. Conclusion: Homocysteine levels and folate deficiency are reliable indicators of PPROM risk. Elevated homocysteine is a contributing risk factor.